Dr. Seuss: The Nose Book - Perkins, Al.; McKie, Roy. (New York : Random House, 1970)
Noses are interesting and serve many purposes including the one of holding up glasses.
Keywords: Stories in rhyme; Juvenile literature; Early Chapter Book